Evaluation of postoperative orientation of the knee and ankle joint after open wedge high tibial osteotomy - Fumiyoshi Kawashima; Hiroshi Takagi (Elsevier, 2022)
Background: Cases with varus knee osteoarthritis (OA) often present concomitant ankle joint deformity and poor tibial plafond inclination (TPI) in the coronal plane. Although changes to the TPI with respect to the ground after open wedge high tibial osteotomy (OWHTO) have been described, reports on the relationship between the correction angle and severity of knee joint line obliquity (KJLO) are scarce. This study aimed to examine the correlation between the correction angle after OWHTO and the change in knee and ankle inclination with respect to the floor. Methods: Between January 2016 and December 2019, 39 knees in 39 patients (mean age, 58.3 ± 9.7 years; male, 14 knees; female, 25 knees) underwent OWHTO for varus knee OA. The mean duration of follow up was 30.1 ± 9.8 months. Radiological severity of OA was evaluated for those with Kellgren-Lawrence grade 1-3. Preoperative and 1-year postoperative radiographs were used to examine the postoperative femorotibial angle, hip-knee angle, KJLO, TPI, talar tilt (TT), position of weight bearing line of the tibial plateau width (WBL ratio; %), and the relationship between the pre-to postoperative changes in each measured value and intraoperative correction angle. The relationship between the pre-to postoperative changes in each measured value and intraoperative correction angle were evaluated. Clinical evaluations were conducted before and 2 years after OWHTO using the Knee Injury and Osteoarthritis Outcome Score (KOOS) subscale of pain. Results: The mean pre-to post-operative changes were 3.2 ± 2.2 for KJLO and 3.1 ± 2.5 for TPI, both demonstrating significant differences as well as significant correlations with the correction angle. The knee joint demonstrated postoperative changes in the valgus direction and none in the varus direction with respect to the floor in all cases. Furthermore, the sum of changes to the KJLO and TPI showed a positive correlation that approximates the change in the correction angle. The mean pre- and postoperative 2-year KOOS subscale of pain were 50.2 ± 10.2 and 82.3 ± 9.1. There were no correlations between preoperative TPI, pre-to postoperative change in TPI, and 2-year postoperative of KOOS subscale of pain. Conclusion: For those who underwent OWHTO for varus OA, the knee joint changed from a preoperative varus malalignment to mild valgus malalignment, and the ankle joint tended to improve from a preoperative valgus malalignment to the postoperative neutral alignment with respect to the floor. Although a positive correlation was found in which the correction angle approximates the sum of changes to the KJLO and TPI, no significant difference was found between changes in KJLO and TPI nor in the ratio between the correction angle and changes in each measured value.